The Effect of Promotion on The Interest of Buying Women's Products in Women's Saves and Loans in Returning Fund Management Units Tomo District, Sumedang Regency - Heni Anggraeni; Sukmayadi; Cahyono (Journal of Bussines Management Basic, 2022)
Promotion is an important aspect of the marketing mix that supports sales success. Promotion is used to introduce products to the wider community so that there will be buying interest in a company product so that its use increases. Based on this, this study aims to determine the effect of promotion on the interest in buying savings and loan products for women's groups in the Revolving Fund Management Unit, Tomo District, Sumedang Regency. This study uses a quantitative research method approach. Sampling was done by simple random sampling with the research sample of the female group. The research data collection was carried out by means of a questionnaire, documentation and observation. The research data were analyzed using statistical analysis through simple regression test, correlation coefficient test, determination coefficient test and t test. The results of the study explain that promotion has a strong relationship with purchase intention as indicated by the correlation coefficient of 0.715 then promotion has a positive and significant effect on purchase intention. This is indicated by the regression equation model Y = 21.912 + 0.429X, the significance value is smaller than the 0.05 level and the t count (9.016) is greater than the t table (0.678). Furthermore, based on the coefficient of determination test, promotion has an effect of 51.1% on purchase intention, while 48.9% is influenced by other factors not examined.